Gender and Empire : The Role of Female Monarchs in Maintaining the British Empire - HACHEMI, Imane; TALBI, Samah (University of Eloued جامعة الوادي, 2024)
This research discusses the main role of female monarchs that had maintained the British Empire. Despite the dominance of male rulers during the peak development of the United Kingdom and the British Empire, the contribution of female monarchs were crucial in shaping its entire course. However, female governance remains unexplored and overshadowed by their male peers. So, what are their main political, cultural, economic, diplomatic and Military achievements and what did female monarchs do to preserve the empire? In this study analytical descriptive methods were adopted alongside with iconography, contextual and historical source analysis. This Investigation also utilized and analysed both primary sources and secondary sources including articles books and websites data. It was revealed that key historical events in British history were marked during the reign of female monarchs, including the formation of both United Kingdom and the Empire. All female monarchs were diplomatically more successful than many kings. Queen monarchs directly influenced the British Empire while Queen concerts influenced it indirectly, however each exerted powerful effect. Even when the authority of Queens is limited, they can still make significant change. If they were subjected under any certain obligatory circumstances to rule, they would still govern with excellency. The research highlights the importance of analysing female leadership historically and relating it to contemporary policies as valuable lessons of governance. Additionally, the unknown and short reigning Queens are not necessarily politically unsuccessful rulers, their reign requires further scholarly examinations and understanding. هذا البحث يناقش الدور الاساسي لنساء الحاكمات في ظل هيمنه الحكام الذكور خلال ذروه الامبراطوريه البريطانيه كانت مساهمه الملكات الحاكمات لا شك فيها في تشكيل مسار المالملكه باكمله و يظل حكمهن طاغيه عليه دراسات اقرانهن من الذكور الملوك. اذا ما هي اعظم الانجازات السياسيه و الثقافيه والاقتصاديه والدبلوماسيه الاساسيه التي قمن بها ؟ و ماذا فعلن كي يحافضن على الامبراطورية ؟هذا البحث اعتمد على اساليب وصفيه تحليليه تتضمن تحليل ايقونات فنية اضافة إلى سياق و مصادر تاريخيه بالإضافة إلى استخدام وتحليل مصادر اوليه ومصادر ثانويه بما في ذلك الكتب والمواقع الالكترونيه و مقالات تم اكتشافه ان اهم الاحداث تاريخ بريطانيا حدثت اثناء حكم الملكات من بينها تشكل المملكه المتحده والامبراطوريه البريطانيه كل من الحكمات الاناث كن ناجحات دبلوماسيا. على عكس الكثير من الملوك اثرت الملكات الحاكمه في بريطانيا تاريخيه بشكل مباشر واثرت زوجات الملوك بشكل غير مباشر ولكن كان لكل منهما تاثير قوي. بالرغم من سلطه الملكات المحدوده فلا يزال بامكانهن صنع تغير كبير و اذا اجبرت النساء على الحكم تحت اي ظروف معينه او قاسية فحكمهن سيكون مثاليا كما اثبت تاريخيا. يركز هذا البحث ايضا على اثبات اهميه تحليل حكم القائدات النساء تاريخيا وربطه بالسياسات الحديثه كدروس قيمه في الحكم الحديث .ايضا عندما تكون الملكات غير معروفات فهذا لا يعني بالضرورة انهن غير ناجحات سياسيا او تاريخيا فترة حكمهن تحتاج اكثر اهتماما و تحليل.
Literature and Civilization
Keywords: Britain; Consorts; Empire; Monarch; Queens; امبراطورية، بريطانيا، حكام، ملكات